2017
DOI: 10.1126/sciimmunol.aak9573
|View full text |Cite
|
Sign up to set email alerts
|

Lysosome signaling controls the migration of dendritic cells

Abstract: Dendritic cells (DCs) patrol their environment by linking antigen acquisition by macropinocytosis to cell locomotion. DC activation upon bacterial sensing inhibits macropinocytosis and increases DC migration, thus promoting the arrival of DCs to lymph nodes for antigen presentation to T cells. The signaling events that trigger such changes are not fully understood. We show that lysosome signaling plays a critical role in this process. Upon bacterial sensing, lysosomal calcium is released by the ionic channel T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(160 citation statements)
references
References 53 publications
10
149
0
Order By: Relevance
“…TRPML1 was recently described to be required for fast and persistent migration of activated DCs, and TRPML1-deficient mature DCs migrated less efficiently to the draining LNs upon injection into the footpad (46). Due to the lack of TRPML1-specific antibodies for TRPML1 detection by flow cytometry, we confirmed Trpml1 gene editing by sequence trace decomposition and found that two selected Trpml1-targeting sgRNAs (sgRNA 1 and 3) induce gene editing in more than 80% of the Cas9-Hoxb8 cells also expressing the fluorescent marker Cerulean encoded by the same lentivirus (Figure 8A), suggesting that the large majority, if not all, transduced cells has an edited Trpml1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TRPML1 was recently described to be required for fast and persistent migration of activated DCs, and TRPML1-deficient mature DCs migrated less efficiently to the draining LNs upon injection into the footpad (46). Due to the lack of TRPML1-specific antibodies for TRPML1 detection by flow cytometry, we confirmed Trpml1 gene editing by sequence trace decomposition and found that two selected Trpml1-targeting sgRNAs (sgRNA 1 and 3) induce gene editing in more than 80% of the Cas9-Hoxb8 cells also expressing the fluorescent marker Cerulean encoded by the same lentivirus (Figure 8A), suggesting that the large majority, if not all, transduced cells has an edited Trpml1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we also addressed the role of the lysosomal ion channel TRPML1 in homing of lymph-delivered DCs. A recent study reported that TRPML1 is required for persistent migration and chemotaxis of activated DCs and Trpml1 −/− mature DCs were less efficient in migrating to the draining lymph node when transferred into the footpad of recipient mice (46). To clarify whether Trpml1 -deficient DCs are impaired in exiting from peripheral tissue or in exiting from the subcapsular sinus toward the deep T cell zone, we intralymphatically injected Trpml1 -deficient DCs generated from GM-CSF- and LPS-stimulated Cas9-Hoxb8 cells and found that they translocated slower from the SCS to the T cell zone of the LN than Trpml1 +/+ DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, given the interplay between eIF2a phosphorylation and actin polymerization, we wondered whether PERK-deficient cells could display some migratory deficits. We used microfabricated channels, that mimic the confined geometry of the interstitial space in tissues (Heuze et al, 2013, Bretou et al, 2017, to find that PERK-deficient cells were not able to increase their migration speed in response to LPS (Fig. 9G), confirming the link between eIF2a phosphorylation and actin dynamics.…”
Section: Perk and Actin Polymerization Coordinates P-eif2α Levels Andmentioning
confidence: 83%
“…Lipopolysaccharide (LPS) detection by Toll-Like-Receptor 4 (TLR4) promotes DCs maturation by triggering a series of signaling cascades resulting in secretion of polarizing and inflammatory cytokines, upregulation of co-stimulatory molecules, as well as enhanced antigen processing and presentation (Mellman, 2013). All these functions are accompanied by major remodeling of membrane trafficking and actin organization to favor both antigen phagocytosis and DC migration to the lymph nodes (West et al, 2004, Bretou et al, 2017, Chabaud et al, 2015, Arguello et al, 2016. TLR4 is particularly expressed in the group 2 of conventional DCs (cDC2), characterized by the expression of surface CD11c, CD172a, as well as CD11b and endowed with a strong MHC II restricted antigen presentation capacity (Dalod et al, 2014).…”
Section: Introductionmentioning
confidence: 99%